Reinstatement of Quercus tungmaiensis Y.T. Chang (Fagaceae) and supplementation of its anatomic features - Deng, Min; Coombes, Allen; Li, Qiansheng (Phytotaxa, 2015)
Leaf architecture and epidermis features are useful to reveal the taxonomic identities of species in Quercus s.l.. For many years different opinions have existed on the taxonomic status of Quercus tungmaiensis, either as a synonym of Q. lanata or as an independent species. In this study, we compared the leaf epidermal features, leaf architecture and other morphological features of Q. tungmaiensis and Q. lanata. Our results revealed that the dense persistent stellate trichomes with a compound trichome base, uniseriate trichomes on the abaxial leaf surface, blunt-tipped teeth and well developed areoles formed by the 5° veins, in Q. lanata were different to the glabrous abaxial leaf surface, spine-tipped teeth and areoles formed by the 4° veins of Q. tungmaiensis. Therefore, the name Q. tungmaiensis should be reinstated. Its systematic placement in section Ilex was further discussed. A key to Q. tungmaiensis and other common evergreen oaks of section Ilex in East Asia was provided.